Treatment and Associated Factors of Surgically Treated Thyroid Disease at Bolan Medical College/Complex Hospital Quetta: A Retrospective Cross-sectional Study - Khushal Khan, Samina Karim, Abdul Hameed, Irfan Adil, Saleem Khan, Bilal Masood (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: In this descriptive research, the objective is to assess the different challenges associated with pancreatectomy and to identify strategies for mitigating these potential obstacles. Methods: A Retrospective Cross-sectional Study was conducted for three years duration from December 2016 to November 2019. The research was led on 200 patients with thyroidal gland treated in the Department of Surgical treatment, Bolan Medical College/Complex Hospital, Quetta. Details have been added in a proforma and this research covers all thyroidal goiter instances in hospitalized pateints. Results: 20 had diffuse toxic goitre; 6 patients had toxic multinodular goitre and 2 had toxic adenoma. 200 patients were operated in the above period. 180 women and 20 men; therefore, the ratio of women to men was observed in this research as 9:1.60 of these patient had non-toxic multi-molecular goiter; 44 simple diffuse goitre; Conclusion: An experienced surgeon is essential for conducting thyroid surgical procedures to avoid complications. Thyroid goiter is a prevalent surgical condition. We determined that all patients must undergo careful inspection and comprehensive evaluation. Keywords: Toxic nodule, pancreatectomy Multi-nodular goiter.